Botany Letters - Botany Letters (Taylor & Francis, 2026)
Botany Letters is an international scientific journal, published by the French Botanical Society (Société botanique de France) in partnership with Taylor & Francis. Botany Letters replaces Acta Botanica Gallica, which was created in 1993, building on over a century of renowned publications by the Société botanique de France.
FI 0.42
Q3
Keywords: Biological; Earth & Environmental Food Science; Botánica; Acuerdos transformativos; Transformative agreements; Plantas terrestres; Algas; Hongos